Application of salicylic acid in growing beta vulgaris l. plants in the context of sustainable agricultural production - Tsvilynyuk, Olga; Telehii, Liliia (Видавництво Львівської політехніки, 2021)
The use of synthetic phytohormones is a promising technology for intensification and greening of agricultural production. Salicylic acid, among the others, is of particular interest. It causes anti-stress activity in plants in response to various adverse environmental factors in the laboratory. The analysis of the results of model field experiments showed that the use of salicylic acid for pre-sowing treatment of beet seeds varieties “Detroit” and “Egyptian flat” improves the habitus of mature plants, increases their water conservation capacity under adverse growth conditions (concentration 1∙10-4 M). In adverse climatic conditions (initially excess moisture, and during the period of active growth and accumulation of nutrients – drought), the mass of the roots of both varieties of beets doubled under the influence of salicylic acid at a concentration of 1∙10-5 M and increased 1.7 times at a concentration of 1∙10-4 M (Detroit beets). This indicates a variety-specific reaction of beet plants to different concentrations of salicylic acid used for pre-sowing seed treatment. The use of salicylic acid in the cultivation of beets can become a priority in the transition of agriculture to the principles of sustainable development in a changing climate.
Keywords: beets; salicylic acid (SA); drought; water holding capacity; root mass